2011
DOI: 10.1016/j.fuel.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Fuel effect on the liquid-phase penetration of an evaporating spray under transient diesel-like conditions

Abstract: ElsevierPastor Soriano, JV.; García Oliver, JM.; Nerva, J.; Giménez, B. (2011). Fuel effect on the liquid-phase penetration of an evaporating spray under transient diesel-like conditions. Fuel. 90 (11) AbstractMeasurements of the maximum liquid-phase penetration have been performed injecting five different fuels through a single-hole nozzle in an optical engine under a large set of thermodynamic and injection conditions. The focus of this paper is twofold. First, it pretends to study fuel physical properties

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Both results are corroborating this effect as the cylinder charge pressure, temperature, and density are increasing as the SOI is closer to the TDC. This behavior is consistent with previous studies on liquid-fuel penetration in diesel engine [29][30][31].…”
Section: Spray Visualizationsupporting
confidence: 93%
“…Both results are corroborating this effect as the cylinder charge pressure, temperature, and density are increasing as the SOI is closer to the TDC. This behavior is consistent with previous studies on liquid-fuel penetration in diesel engine [29][30][31].…”
Section: Spray Visualizationsupporting
confidence: 93%
“…A very important factor toward the goal of using cetane fuels in direct injection diesel engines is to characterize of fuel spray [15], [16], [17], [18]. Air fuel mixing is strongly influenced by the spray behavior and fuel properties, therefore the performance of a diesel engine and the requirements discussed in the previous paragraphs for new combustion modes depend on the fuel air distribution within the mixture [19], [20].…”
Section: Most Of the New Combustion Modes Developed Recently To Reducmentioning
confidence: 99%
“…Recent studies performed under high-temperature, but non-reactive, unsteady conditions showed that biodiesel can increases LL by up to 20% [5,6] or 100% [7] with respect to conventional diesel fuels. This behavior has been related to its higher density and lower volatility [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies performed under high-temperature, but non-reactive, unsteady conditions showed that biodiesel can increases LL by up to 20% [5,6] or 100% [7] with respect to conventional diesel fuels. This behavior has been related to its higher density and lower volatility [7,8]. Because of the longer liquid penetration, the proximity of the liquid-phase spray to the quasi-steady flame lift-off length (LOL) is increased, which can potentially modify combustion and emissions formation [10].…”
Section: Introductionmentioning
confidence: 99%